Pancreatoblastoma: Cytologic and histologic analysis of 12 adult cases reveals helpful criteria in their diagnosis and distinction from common mimics. Issue 11 (3rd October 2019) - Reid, Michelle D.; Bhattarai, Shristi; Graham, Rondell P.; Pehlivanoglu, Burcin; Sigel, Carlie S.; Shi, Jiaqi; Saqi, Anjali; Shirazi, Maryam; Xue, Yue; Basturk, Olca; Adsay, Volkan
Abstract : Background: Pancreatoblastoma (PBL) is a rare malignant pancreatic tumor seen predominantly in childhood, and its cytologic diagnosis remains challenging. Methods: Twelve fine‐needle‐aspirations from 11 adults were analyzed. Results: In total, 6 men and 5 women (median age, 45 years; age range, 32‐60 years) had tumors measuring a median 5.6 cm (range, 2.5‐12 cm) located in the pancreatic head (n = 7) or tail (n = 4), including 3 with familial adenomatous polyposis (FAP)/FAP‐related syndromes and 4 with metastasis at diagnosis. The median follow‐up was 39.8 months (range, 0.8‐348 months), and 5 patients died of disease. The original cytology diagnoses were: PBL (n = 2), neuroendocrine neoplasm (n = 2), poorly differentiated neuroendocrine carcinoma (n = 2), well differentiated neuroendocrine tumor (n = 1), poorly differentiated carcinoma (n = 2), "positive for malignancy" (n = 1), acinar cell carcinoma (n = 1), and epithelioid neoplasm with endocrine and acinar differentiation versus PBL (n = 1). Universal cytopathologic findings included hypercellularity; 3‐dimensional clusters; and single, monotonous, blast‐like cells that were from 1.5 to 2.0 times the size of red blood cells with high nuclear‐to‐cytoplasmic ratio, fine chromatin, small, distinct nucleoli, and a resemblance to well differentiated neuroendocrine tumor and poorly differentiated neuroendocrine carcinoma. Branching pseudopapillae (n = 7) and grooved nuclei (n = 3) raised the differential diagnosis of solid‐pseudopapillary neoplasm, but with more atypia. Uncommon features included pleomorphism (n = 4) and numerous mitoses (n = 1). Squamoid morules were seen on smears (n = 5) or cell blocks (n = 6) in 70% of patients and were characterized by epithelioid cells with elongated, streaming nuclei, fine chromatin, absent nucleoli, and positive nuclear β‐catenin (n = 6 of 8). The median Ki‐67 index was 21% (range, 2%‐70%), and neuroendocrine marker expression was common (100%), but acinar markers were variable (63%). Conclusions: A combination of cytologic findings in PBL, including a predominant population of primitive blast‐like cells, subtle squamoid morules, frequent neuroendocrine and variable acinar phenotype, should facilitate accurate cytologic diagnosis and distinction from common mimics. Abstract : The defining cytologic characteristics of pancreatoblastoma may be subtle but are helpful in distinguishing it from other solid, cellular, stroma‐poor pancreatic neoplasms, for which it is often mistaken. In this study, fine‐needle aspiration findings in pancreatoblastoma included primitive blast‐like cells and subtle squamoid morules, which, along with multilineage differentiation, should allow its distinction from mimics.